Achieving Sustainable Digital Transformation in TVET Institutions through Enterprise Architecture - Hussein, Surya Sumarni; Ramly, Norlida; Wan Ahmad, Wan Azlin Zurita; Mohammed Ridzuan, Muhammad Irfan Arif; Salehen, Puteh Melor Wesma; Dang, Duong (Journal of Technical Education and Training, 2024)
The approach of Enterprise Architecture (EA) in Technical and Vocational Education and Training (TVET) institutions holds significant potential for the institution’s digital transformation. This study explores key factors to sustain digital transformation in TVET Institutions using a Systematic Literature Review (SLR) and semi-structured interviews. The SLR provides a comprehensive overview of existing literature on EA in educational contexts, focusing on its role in aligning institutional goals with industry requirements. Common themes and research gaps identified through this review set the stage for empirical investigation. Interviews with IT administrators, academia, and experts offer practical insights into the challenges and opportunities associated with EA implementation in TVET institutions, validating findings from the literature and uncovering unique contextual factors relevant to TVET institutions in Malaysia. The thematic analysis highlights several key factors, namely, management support and their involvement, a clear business vision and goal strategy, and the adoption of emerging technologies such as Artificial Intelligence and the Internet of Things towards sustainable digital transformation in TVET institutions. The findings indicate that a well-implemented EA framework can significantly drive the digital transformation of TVET institutions, leading to better-prepared graduates and a more adaptable workforce. This study provides a detailed analysis of the key factors to sustain digital transformation in TVET Institutions and offers practical recommendations for policymakers and educational leaders. The insights gained can guide future initiatives aimed at the digital transformation of TVET institutions, contributing to a more competitive and responsive educational sector in Malaysia.